2020
DOI: 10.7759/cureus.6660
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Triple Neurotization Technique as a Single Procedure in Adult Traumatic Brachial Plexus Injury

Abstract: Introduction: Brachial plexus injuries are common and result in significant disabilities. This study evaluated the outcome of triple neurotization as a single procedure for upper trunk brachial plexus injury. Patients and Methods: Some 25 adult consecutive patients with injured upper trunk brachial plexus who underwent microscopic reconstructive surgery using triple neurotization technique in the authors' institute were recruited in this study. Data on operative and functional outcomes were captured. Modified … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 24 publications
0
4
0
Order By: Relevance
“…In studies that investigated DNT procedures, the mean recovery of ≥M4 shoulder abduction ranged from 30% to 88.9%, 10 , 13 , 14 , 15 , 18 and the mean ROM ranged from 92º to 115º. 11 , 12 , 13 , 14 , 15 , 16 , 17 The mean recovery of ≥M4 external rotation ranged from 20% to 60%, with a mean ROM ranging from 54º to 136º. 11 , 12 , 13 , 14 , 15 , 16 , 17 In this case series, the results of the DNT for shoulder abduction were similar to published literature, reaching a mean of 99º with 69% of patients experiencing recovery ≥M4 and a mean of 69º of external rotation with 52% of patients having ≥M4 recovery.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In studies that investigated DNT procedures, the mean recovery of ≥M4 shoulder abduction ranged from 30% to 88.9%, 10 , 13 , 14 , 15 , 18 and the mean ROM ranged from 92º to 115º. 11 , 12 , 13 , 14 , 15 , 16 , 17 The mean recovery of ≥M4 external rotation ranged from 20% to 60%, with a mean ROM ranging from 54º to 136º. 11 , 12 , 13 , 14 , 15 , 16 , 17 In this case series, the results of the DNT for shoulder abduction were similar to published literature, reaching a mean of 99º with 69% of patients experiencing recovery ≥M4 and a mean of 69º of external rotation with 52% of patients having ≥M4 recovery.…”
Section: Discussionmentioning
confidence: 99%
“…Several authors have reported increased shoulder function after double nerve transfer (DNT) with the intercostal nerve 12 and median or ulnar nerve 13 as nerve donors and the axillary nerve as the target nerve. 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 Cardenas et al 19 in their study in 2008 reported that the more nerves transferred, the higher the abduction range in restoring shoulder function. Similar studies comparing SNT with DNT reported a greater shoulder range of motion (ROM) or a higher recovery rate of ≥M4 for shoulder function with DNT.…”
mentioning
confidence: 99%
“…The time interval between the injury and the surgical intervention is one of the main factors that guide the therapeutic algorithm [5,15]. The best functional outcomes can be achieved via primary nerve reconstruction comprising direct nerve repair, neurolysis for scar compression, nerve grafting, and nerve transfers performed no later than six months following injury [16][17].…”
Section: Introductionmentioning
confidence: 99%
“…The best functional outcomes can be achieved via primary nerve reconstruction comprising direct nerve repair, neurolysis for scar compression, nerve grafting, and nerve transfers performed no later than six months following injury [16][17]. As a result of interruption of the motor innervation, a time-dependent irreversible degeneration commences at the motor endplate [5,15]. Reinnervation procedures performed 18-24 months following injury usually result in a functionless muscle [18][19].…”
Section: Introductionmentioning
confidence: 99%